An Assessment of the Productivity Challenges Experienced by Manufacturing Small Micro Medium Enterprises During Lockdown - MPANZA, SINAKHOKONKE (LPPM of NAROTAMA UNIVERSITY, 2026)
The focus of this study was to examine productivity issues experienced by small, medium and micro enterprises (SMMEs) in the manufacturing sector in Ekurhuleni Municipality during COVID?19 lockdown restrictions, more particularly focusing on internal and external environment factors influencing the productivity challenges in manufacturing SMMEs.The research also sought to identify and investigate internal and external environmental variables that affected the productivity and sustainability of manufacturing SMMEs in Ekurhuleni Municipality. The study showed a clear distinction between the importance that was placed on having access to technological production management tools, and knowledge of internal and external factors affecting productivity. In addition, this study confirmed that South African SMMEs confront significant difficulties in the context of small businesses. A simple random sampling method was used to select the respondents. A total of 300 questionnaires were distributed to the target population with 223 questionnaires being completed and returned. The questionnaire was used to determine manufacturing SMMEs’ perceptions of their companies’ access to technological production management equipment and their knowledge of the company’s internal and external elements. Based on the empirical findings, the study identified that both internal and external environmental factors such as size of the firm, firm age, resources for training needs, technology and government support have a critical influence towards the productivity challenges faced by SMMEs. It is recommended that a study be conducted to investigate the impact of manufacturing SMMEs’ productivity on their business performance, growth and sustainability.